Relationship between Blood Pressure and Urine Protein in Preeclampsia at Prima Husada Hospital Sidoarjo : Hubungan Tekanan Darah Dengan Protein Urine Pada Kejadian Preeklamsia Di RSU Prima Husada Sidoarjo - Santoso, Andreas Putro Ragil; Masruroh, Nur; Amalia, Ikke Nanda; Santy, Wesiana Heris (Medicra (Journal of Medical Laboratory Science/Technology), 2020)
The problems related to pregnancy and childbirth including maternal and infant mortality rates can’t be removed from another causative factors that arise, one of the second cause from maternal mortality rates is preeclampsia, which is a specific disorder of hypertension caused by pregnancy at gestational age of more than 20 weeks with proteinuria and rarely occurs before 20 weeks gestational except if any kidney or trophoblastic disease. Hypertension and proteinuria to be a symptoms that often appears in preeclampsia diagnose. The relationship between of risk factor occur preeclampsia, that is blood pressure and protein urine which is the important indicator for enforcement of preeclampsia. The purpose of researchis analyze the relationship between of blood pressure and protein urine levels on the incidence of preeclampsia. The type of this research is analytic observational. Sample of this research is pregnant mother with preeclampsia in RSU Prima Husada Sidoarjo. The results use the Correlation Pearson test showed that p value for the systolic blood pressure is 0.791 and the diastolic blood pressure is 0.268, this is shows that blood pressure isn’t related with protein urine.